2018
DOI: 10.5897/jmpr2018.6567
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiviral activity of Brazilian Cerrado plant extracts against animal and human herpesviruses

Abstract: The Brazilian savanna known as "Cerrado" is very rich in medicinal plants that are used by the local population for treatment of several illnesses. The herpesvirus is a serious problem worldwide, and affects both animal and human health. This work aimed to study the antiviral activity of eight extracts from plants natives of "Cerrado" region against human (HSV-1), equine (EqHV-1) and swine herpesviruses (SuHV-1). The results showed that all plant extracts: Banisteriopsis variabilis, Byrsonima intermedia, Campo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Among the species used, Banisteriopsis variabilis, Byrsonima intermedia, Campomanesia xanthocarpa, Erythroxilum deciduum, Lacistema hasslerianum, Ocotea pulchella, Stryphodendron adstringens and Xylopia aromatica were found to have significant effects. It has also been reported that the best effect is seen in B. intermedia [59]. In a study conducted in China, the effect of different extracts of plant species used on HSV-1 was investigated.…”
Section: Herpes Simplex Virus (Hsv-1 Hsv-2) (Genus: Simplexvirus)mentioning
confidence: 99%
“…Among the species used, Banisteriopsis variabilis, Byrsonima intermedia, Campomanesia xanthocarpa, Erythroxilum deciduum, Lacistema hasslerianum, Ocotea pulchella, Stryphodendron adstringens and Xylopia aromatica were found to have significant effects. It has also been reported that the best effect is seen in B. intermedia [59]. In a study conducted in China, the effect of different extracts of plant species used on HSV-1 was investigated.…”
Section: Herpes Simplex Virus (Hsv-1 Hsv-2) (Genus: Simplexvirus)mentioning
confidence: 99%